The Influence of Dimensional Static and Dynamic Charge on the Spectral Parameters and Active Dynamic Conductivity of Resonanse Tunnelling Structures with Constant Electric Field - Boyko, I.V.; Gryschyk, A.M. (Physics and Chemistry of Solid State, 2016)
In the model of effective masses and rectangular potentials obtained self-consistent solution of Poisson and Schrödinger equations for different concentrations of electrons. It has been calculated spectral parameters and active dynamic conductivity for three-well nanostructure as active band of experimental quantum cascade laser. It has been established, that space charge deforms shape dependence of transmission factor of electron energy from Lorentzian shape to quasi-Lorentzian, shifting their maximum value to the high energy region and increasing the lifetimes of electronic quasistationary states. It was shown, that with increasing concentration of electrons energy of laser radiation in quantum transitions and decreases, and the total value of active dynamic conductivity increases so, that it increases the partial contribution component of conductivity, determined by electron flux, directed opposite to the exit of nanostructure.